Carbon-supported metal zinc catalyst and its preparation method and application
By using carbon-supported metal zinc catalysts and high-temperature calcination, the problems of low catalyst activity and harsh reaction conditions in the prior art are solved, and the efficient catalytic synthesis of asymmetric organic carbonates is achieved, reducing production costs and simplifying the process flow.
Patent Information
- Application Number
- CN202411991809.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, when catalyzing biomass-based alcohols to synthesize asymmetric organic carbonates, the catalyst activity is low, the reaction conditions are harsh, and the industrial manufacturing cost is high and the process flow is complex.
A carbon-supported metal zinc catalyst is used, which is prepared by calcining the precursor eutectic solvent and zinc acetate at 500~800°C, and has high catalytic efficiency, selectivity and stability.
The efficient catalytic biomass-based alcohol synthesis of asymmetric organic carbonates is achieved, which reduces production costs, simplifies the process flow, and improves the stability and sustainability of the catalyst.
Smart Images

Figure CN119386848B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysis technology, and more specifically, to a carbon-supported metal zinc catalyst. The present invention also relates to a method for preparing the carbon-supported metal zinc catalyst, and a method for catalyzing biomass-based alcohol to synthesize asymmetric organic carbonates. Background Art
[0002] Simple carbonates such as dimethyl carbonate and diethyl carbonate can be directly converted from carbon dioxide through chemical synthesis. If they can be mass-produced and applied, it will undoubtedly consume carbon dioxide in the atmosphere, and can alleviate the greenhouse effect caused by carbon dioxide to a certain extent. Secondly, low-level carbonates are important raw materials for chemical production. Their non-toxic, harmless, green and degradable properties can replace the production of sulfides and halogenated compounds, and are compounds with great development potential. Asymmetric carbonates are more valuable than symmetric carbonates due to their low flash point and high stability. Low-level carbonates can be controlled to synthesize asymmetric carbonates with different properties through ester exchange reactions with different alcohol compounds, and their industrial application value is extremely high.
[0003] The traditional method for synthesizing asymmetric carbonates is the phosgene method, which uses phosgene (COCl2) and alcohol as raw materials and alkali as catalyst to prepare asymmetric carbonates at room temperature. However, this method usually requires adding different alcohols in batches, which is cumbersome to operate. In addition to obtaining the target product, two symmetric carbonates are also produced, and the reaction selectivity is poor.
[0004] In addition, phosgene itself is a toxic and dangerous chemical that may cause harm to the human body and the environment. Therefore, the green preparation of asymmetric organic carbonates has gradually attracted widespread attention. In the preparation process, catalysts are crucial to promote the transesterification reaction of diethyl carbonate with different alcohols.
[0005] Currently, the catalysts disclosed for preparing asymmetric carbonates still have the problems of low catalyst activity and harsh conditions required for the catalyst reaction. In addition, the synthesis of asymmetric carbonates also has the disadvantages of high industrial manufacturing costs and complicated process flows. Summary of the invention
[0006] In view of the existing technical difficulties, the purpose of the present invention is to provide a carbon-supported metal zinc catalyst with high catalytic efficiency, high selectivity and strong stability.
[0007] The second aspect of the present invention is to provide a method for preparing a carbon-supported metal zinc catalyst.
[0008] The third aspect of the present invention is to provide an application of a carbon-supported metal zinc catalyst in catalyzing the synthesis of asymmetric organic carbonates from biomass-based alcohols, and a method for catalyzing the synthesis of asymmetric organic carbonates from biomass-based alcohols.
[0009] To this end, the first technical solution provided by the present invention is as follows:
[0010] A carbon-supported metal zinc catalyst is prepared by calcining a precursor low eutectic solvent and zinc acetate at 500-800°C.
[0011] Furthermore, in the above-mentioned carbon-supported metal zinc catalyst, the mass ratio of the precursor low eutectic solvent to zinc acetate is (5~10):1.
[0012] Furthermore, in the above-mentioned carbon-supported metal zinc catalyst, the zinc loading amount in the carbon-supported metal zinc catalyst is 5wt%~30wt%.
[0013] Furthermore, the carbon-supported metal zinc catalyst has a surface area of 238-797 m 2 / g; pore diameter 1.7032~3.0968nm, pore volume 0.0272~0.1334cm 3 / g.
[0014] Furthermore, the above-mentioned carbon-supported metal zinc catalyst, the precursor low eutectic solvent is prepared by the following method: polyethylene glycol and 2-methylimidazole are weighed in a mass ratio of 3: (1.8~2.2), placed in a beaker, and mixed and stirred at 80°C until the two are completely mixed.
[0015] The method for preparing a carbon-supported metal zinc catalyst provided by the present invention comprises the following steps in sequence:
[0016] Step 1) Weigh the precursor deep eutectic solvent and zinc acetate according to the mass ratio (5-10):1;
[0017] Step 2) Add the precursor low eutectic solvent into the container, stir and heat to 80°C; Add the weighed zinc acetate into the container of step 2) and mix with the precursor low eutectic solvent, then add ethylene glycol and continue stirring until the zinc acetate solid is completely dissolved, continue stirring for 3 minutes, and stop heating and stirring;
[0018] Step 3) Transfer the solution prepared in step 2) to two small corundum crucibles, place them in a tube furnace after fixing, introduce protective gas, heat up to 500-800°C at a heating rate of 5°C / min, calcine to pyrolysis temperature at this temperature and keep warm for 1.5-2.5h;
[0019] Step 4) Grinding the catalyst obtained in step 3) to obtain a carbon-supported metal zinc catalyst.
[0020] The third technical solution provided by the present invention is to use the above-mentioned carbon-supported metal zinc catalyst to catalyze the synthesis of asymmetric organic carbonates from biomass-based alcohols.
[0021] The above-mentioned method for synthesizing asymmetric organic carbonates from biomass-based alcohols is as follows: biomass-based alcohols, diethyl carbonate, and carbon-supported metal zinc catalyst are added into a flask, reacted at 60-120° C. for 2-4 hours, cooled to room temperature after the reaction, and the liquid is collected for analysis;
[0022] The molar ratio of the biomass-based alcohol, diethyl carbonate and carbon-supported metal zinc is 1:(8-11).
[0023] The molar ratio of the biomass-based alcohol to diethyl carbonate is 1:(7-14).
[0024] The amount of the carbon-supported metal zinc catalyst used is 3% to 6% of the total mass of the raw materials for preparing the asymmetric organic carbonate.
[0025] Furthermore, in the method for synthesizing asymmetric organic carbonates from the above-mentioned biomass-based alcohol, the biomass-based alcohol is one of n-hexanol, benzyl alcohol, tetrahydrofurfuryl alcohol, 2-ethylhexanol, 2-ethyl-1-butanol, cyclohexanol, n-hexanol, and menthol.
[0026] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0027] The catalyst of the present invention adopts a precursor low eutectic solvent and has the characteristics of low toxicity, sustainability, recyclability and biodegradability; the use of ethylene glycol as a solvent can completely dissolve zinc acetate in the solution, thereby achieving uniform distribution of metal Zn.
[0028] The catalyst of the present invention has low production cost and high reaction activity, and can effectively promote the reaction process under the condition of low dosage.
[0029] The catalyst of the invention utilizes a precursor low eutectic solvent to introduce non-noble metal Zn and is prepared by high-temperature calcination. The cubic surface of the catalyst is smooth and flat, the configuration is regular, and the catalyst has high catalytic activity and selectivity when catalyzing asymmetric organic carbonates. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the carbon-supported metal zinc catalyst of Example 1 of the present invention;
[0031] Figure 2 This is a TEM image of the carbon-supported metal zinc catalyst of Example 1 of the present invention;
[0032] Figure 3 This is the XRD diagram of the carbon-supported metal zinc catalyst of Example 1 of the present invention;
[0033] Figure 4 This is a diagram of the cyclic experimental test of carbon-supported metal zinc catalyst. DETAILED DESCRIPTION
[0034] The present invention will be described clearly and completely below in conjunction with the embodiments and drawings of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0035] In the following examples of the present invention, the content of asymmetric organic carbonate and the conversion rate of biomass-based alcohol were measured by gas chromatography.
[0036] The precursor low eutectic solvent described in the following examples is prepared by the following method: polyethylene glycol and 2-methylimidazole are weighed in a mass ratio of 3:2, placed in a beaker, and mixed and stirred at 80° C. until the two are completely mixed. Example 1
[0037] This embodiment provides a carbon-supported metallic zinc catalyst, wherein the catalyst zinc loading amount is 5 wt %.
[0038] The carbon-supported metal zinc catalyst is prepared by the following methods in sequence:
[0039] 1) Weigh 20g of the precursor deep eutectic solvent (DES) and add it to a 500mL beaker. Add a stirring magnet to the biscuit, then place the beaker on a magnetic stirring and heating machine, set the preheating temperature to 80℃, and heat at a speed of 400 r / min while stirring continuously. After the temperature rises to 80℃, add 2.5g of zinc acetate solid and stir to mix evenly.
[0040] 2) Add 5 g of ethylene glycol to step 1) and continue stirring until the zinc acetate solid is completely dissolved, continue stirring for 3 minutes, stop heating and stirring to obtain a mixed solution;
[0041] 3) Pour the mixed solution prepared in step 2) into a corundum crucible, then place it in the center of a tube furnace, introduce argon at 50 ml / min, heat the temperature to 600°C at a heating rate of 5°C / min, and bake at 600°C for 2 hours. After cooling naturally to room temperature, turn off the argon, open the tube furnace, take out the small corundum crucible, and grind the obtained solid to obtain a carbon-supported metal zinc catalyst.
[0042] The specific surface area of the carbon-supported metal zinc catalyst was 436 m 2 / g, average pore diameter 1.7032nm, pore volume 0.0272cm 3 / g.
[0043] The SEM image of the carbon-supported metal zinc catalyst prepared in Example 1 is shown in Figure 1 , TEM images refer to Figure 2 , XRD pattern see Figure 3 .pass Figure 1 and Figure 2 The morphological characteristics of the carbon-supported zinc catalyst calcined at 600°C can be clearly observed. Its cubic surface is smooth and flat, and its configuration is regular, which means that the active sites on the catalyst surface are more evenly distributed, reducing the unevenness of active sites caused by the irregular surface, thereby improving the catalytic activity. At the same time, the regular configuration and smooth surface also reduce the agglomeration of particles, maintaining the dispersion and stability of the catalyst. TEM testing further shows that no large-scale aggregation of zinc is found in the carbon-supported zinc catalyst, proving that zinc is evenly distributed in the catalyst, making the catalyst highly active during the reaction. Figure 3 This indicates that the catalyst provided in the present application has good crystallinity, and the diffraction peak clearly shows the characteristic peak of zinc, further confirming the uniform dispersion of zinc in the catalyst. Example 2
[0044] The preparation process and parameters of the carbon-supported metal zinc catalyst provided in this embodiment are substantially the same as those in Example 1, except that the carbon-supported metal zinc catalyst is prepared by calcining at 500°C. Example 3
[0045] The preparation process and parameters of the carbon-supported metal zinc catalyst provided in this embodiment are substantially the same as those in Example 1, except that the carbon-supported metal zinc catalyst is prepared by calcining at 700°C. Example 4
[0046] The preparation process and parameters of the carbon-supported metal zinc catalyst provided in this embodiment are substantially the same as those in Example 1, except that the carbon-supported metal zinc catalyst is prepared by calcining at 800°C.
[0047] The BET surface area, pore size and pore volume test methods of the carbon-supported metal zinc catalysts prepared in Examples 2 to 4 are the same as the test methods provided in Example 1. The test results are shown in Table 1.
[0048] Table 1
[0049] catalyst Catalyst pyrolysis temperature (℃) <![CDATA[BET surface area (m 2 / g)]]> Pore size (nm) <![CDATA[Pore volume (cm 3 / g)]]> Example 2 500 797 1.8462 0.0844 Example 3 700 378 1.8571 0.0492 Example 4 800 238 3.0968 0.1334
[0050] Application Example 1
[0051] This application example provides a method for synthesizing an asymmetric organic carbonate using the catalyst prepared in Example 1, and the method is specifically as follows:
[0052] Weigh 2 mmol of n-hexanol, 4 g of diethyl carbonate and 100 mg of the carbon-supported metal zinc catalyst provided in Example 1 into a 25 ml round-bottom flask, and add a small stirrer. Then connect the flask to a serpentine condenser and place it in an oil bath at 120°C and a rotation speed of 600 r / min to react for 5 hours. After the reaction is completed, cool it to room temperature, collect the liquid and detect it by gas chromatography. The specific parameters are shown in Table 2 below.
[0053] Application Examples 2~4
[0054] Application Examples 2 to 4 provide a method for synthesizing asymmetric organic carbonates from n-hexanol using any one of the catalysts prepared in Examples 2 to 4 instead of the carbon-supported metal zinc catalyst in Application Example 1. Other preparation steps and process parameters are the same as those in Application Example 1.
[0055] When the methods provided in Examples 1 to 4 are used to prepare asymmetric organic carbonates, the conversion rate of n-hexanol and the selectivity of asymmetric carbonates are shown in Table 2.
[0056] Table 2
[0057] project catalyst Conversion rate (%) Selectivity of asymmetric carbonate (%) Application Example 1 Example 1 99 99 Application Example 2 Example 2 37 96 Application Example 3 Example 3 96 98 Application Example 4 Example 4 93 97
[0058] Application Examples 5~8
[0059] Application Examples 5 to 8 provide a method for synthesizing asymmetric organic carbonates using different biomass-based alcohols catalyzed by the carbon-supported metal zinc catalyst prepared in Example 1. The preparation steps and parameters are basically the same as those in Application Example 1, except that different biomass-based alcohols are used. For specific parameters in the preparation process, see Table 3.
[0060] Table 3
[0061] project Biomass-based alcohol Catalyst dosage (mg) Reaction temperature (℃) Reaction time (h) Application Example 5 Benzyl alcohol 100 120℃ 5h Application Example 6 Tetrahydrofurfuryl alcohol 100 120℃ 5h Application Example 7 2-Ethyl-1-butanol 100 120℃ 5h Application Example 8 Cyclohexanol 100 120℃ 5h
[0062] When the methods provided in Examples 5 to 8 are used to prepare asymmetric organic carbonates, the biomass-based alcohol conversion rate and the selectivity of asymmetric carbonates are shown in Table 4.
[0063] Table 4
[0064] project catalyst Conversion rate (%) Selectivity of asymmetric carbonate (%) Application Example 6 Example 1 90 96 Application Example 7 Example 1 96 99 Application Example 8 Example 1 80 97
[0065] It can be seen from Table 2 and Table 4 that the carbon-supported metal zinc catalyst provided by the present invention has a highly efficient catalytic ability and excellent selectivity in the ester exchange reaction of synthesizing asymmetric carbonates from biomass-based alcohols.
[0066] In addition, the carbon-supported metal zinc catalyst provided by the present invention has high universality and can maintain high activity for most biomass-based alcohols; among them, n-hexanol has the highest conversion rate; the main reason why the catalyst provided by the present application has different activities for different alcohols is caused by the size of the alcohol molecule. After the hydroxyl group of the alcohol molecule is activated by the carbon-supported metal catalyst, it will preferentially attack the carbonyl carbon atom of diethyl carbonate. Therefore, the size of the alcohol molecule directly determines the difficulty of the attack, thereby determining the reaction activity and the conversion rate of the alcohol.
[0067] Application Examples 9~12
[0068] Application Examples 9 to 12 provide methods for catalyzing asymmetric organic carbonates using the carbon-supported metal zinc catalyst prepared in Example 1. The preparation process and parameters are basically the same as those in Application Example 1, except that the amount of catalyst used, the reaction temperature, and the reaction time are different. For specific parameters, see Table 5.
[0069] Table 5
[0070] project catalyst Biomass-based alcohol Catalyst dosage (mg) Reaction temperature (℃) Reaction time (h) Application Example 9 Example 1 n-Hexanol 40 120℃ 5h Application Example 10 Example 1 n-Hexanol 100 120℃ 3h Application Example 11 Example 1 n-Hexanol 100 60℃ 5h Application Example 12 Example 1 n-Hexanol 100 100℃ 5h
[0071] When the methods provided in Examples 9 to 12 are used to prepare asymmetric organic carbonates, the biomass-based alcohol conversion rate and the selectivity of asymmetric carbonates are shown in Table 6.
[0072] Table 6
[0073] catalyst Biomass-based alcohol (℃) Conversion rate (%) Selectivity of asymmetric carbonate (%) Application Example 9 n-Hexanol 70 99 Application Example 10 n-Hexanol 68 99 Application Example 11 n-Hexanol 65 98 Application Example 12 n-Hexanol 85 99
[0074] It can be seen from Application Examples 1, 9 to 12 that the optimal reaction conditions for the synthesis of asymmetric organic carbonates catalyzed by the catalyst provided in the present application are: normal pressure; temperature, 120° C.; time, 5 h; catalyst dosage, 100 mg.
[0075] Comparative Example 1
[0076] The preparation process and parameters of the carbon-supported metal zinc catalyst provided in this comparative example are basically the same as those in Example 1, except that the carbon-supported metal zinc catalyst is prepared by calcination at 400°C; BET test shows that the specific surface area of the catalyst calcined at 400°C is 963 m 2 / g, average pore diameter 1.7964nm, pore volume 0.0715cm 3 / g.
[0077] Comparative Example 2
[0078] The carbon-supported metal zinc catalyst of this comparative example was prepared by the following method:
[0079] Weigh 5g of lignin (dealkalized) and 5g of zinc acetate in a mortar and grind them into fine powder to mix the components of the sample evenly. Then put the sample into a corundum crucible, put it into a tube furnace after fixing, and introduce argon protective gas, heat it to 600°C at a heating rate of 5°C / min, calcine it to the pyrolysis temperature at this temperature and keep it warm for 2h, turn off the argon gas after it cools down to room temperature naturally, open the tube furnace, take out the corundum crucible, grind the obtained solid to obtain the catalyst.
[0080] Comparative application example 1
[0081] This comparative application example provides a method for synthesizing an asymmetric organic carbonate by catalyzing n-hexanol with the catalyst described in Comparative Example 1, the method comprising the following steps:
[0082] 2mmol of n-hexanol, 4g of diethyl carbonate and 100mg of the carbon-supported metal catalyst provided in Comparative Example 1 were weighed and placed in a 25ml round-bottom flask, and a small stirrer was added; the flask was then connected to a serpentine condenser and placed in an oil bath at 120°C and a speed of 600r / min for 5h. After the reaction was completed, it was cooled to room temperature, and the collected liquid was tested by gas chromatography. The conversion rate of n-hexanol was 0%, and the selectivity of asymmetric carbonate was 0%. It can be seen that the catalyst calcined at 400°C had almost no reaction activity, so the substrate conversion rate of the transesterification reaction was almost zero.
[0083] Comparative Application Example 2-4
[0084] Comparative Application Examples 2-4 provide a method for catalyzing asymmetric organic carbonates under different conditions using the carbon-supported metal zinc catalyst prepared in Example 1. The preparation process and parameters are basically the same as those in Application Example 1. The difference lies in the specific parameters (catalyst dosage, reaction temperature, reaction time) during the reaction. See Table 7 for details.
[0085] Comparative Application Example 5
[0086] The comparative application example provides a method for synthesizing an asymmetric organic carbonate from n-hexanol using the catalyst described in comparative example 2. The preparation process is basically the same as that of application example 1, except that the type of catalyst is different. See Table 7 for details.
[0087] Table 7
[0088] project catalyst Biomass-based alcohol Catalyst dosage (mg) Reaction temperature (℃) Reaction time (h) Comparative Application Example 2 Example 1 n-Hexanol 20 120℃ 5h Comparative Application Example 3 Example 1 n-Hexanol 100 120℃ 1h Comparative Application Example 4 Example 1 n-Hexanol 100 40℃ 5h Comparative Application Example 5 Comparative Example 2 n-Hexanol 100 120℃ 5h
[0089] When the methods provided in Comparative Application Examples 2 to 5 were used to prepare asymmetric organic carbonates, the biomass-based alcohol conversion rate and the selectivity of asymmetric carbonates were shown in Table 8.
[0090] Table 8
[0091] project Conversion rate (%) Selectivity of asymmetric carbonate (%) Comparative Application Example 2 48 98 Comparative Application Example 3 40 96 Comparative Application Example 4 1 97 Comparative Application Example 5 3 97
[0092] It can be seen from Tables 6 and 8 that at a reaction temperature of 40 °C, the conversion rate of alcohol is almost zero. After the temperature is raised to 60 °C, the conversion rate of diethyl carbonate is increased to about 65%. Therefore, it can be explained that under the catalysis of the carbon-supported metal catalyst, the ester exchange reaction of diethyl carbonate at a relatively low temperature, the hydroxyl groups of the alcohol compounds are basically not activated, and therefore the degree of reaction with diethyl carbonate is extremely low.
[0093] At the same time, the amount of catalyst is also an important factor affecting the ester exchange reaction; when the catalyst dosage is 20 mg, the alcohol conversion rate is only 48%, and the conversion rate of alcohol reaches 100% when the catalyst dosage is further increased to 100 mg.
[0094] In order to verify the reusability of the catalyst provided by the present invention, the carbon-supported metal zinc catalyst prepared in Example 1 was tested for performance repeatability. The test method is as follows:
[0095] The solution after the reaction was separated from the catalyst by centrifugation, washed with isopropanol three times, and then freeze-dried for 15 hours (freezing for 12 hours and then drying under freeze vacuum conditions for 3 hours). After drying, the preparation method of Example 1 was followed and the reaction was recycled for three times. The results are shown in FIG. Figure 4 ,Depend on Figure 4 It can be seen that after the catalyst was recycled and reused three times, its activity for the ester exchange reaction of asymmetric carbonates remained basically unchanged, indicating that the catalyst had good stability.
[0096] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for synthesizing asymmetric organic carbonates from biomass-based alcohols, characterized in that: Add biomass-based alcohol, diethyl carbonate, and carbon-supported metal zinc catalyst into a flask and react at 60-120°C for 2-4 hours. After the reaction is completed, cool to room temperature and collect the liquid for analysis. The molar ratio of the biomass-based alcohol to diethyl carbonate is 1:(7-14); The amount of the carbon-supported metal zinc catalyst used is 3% to 6% of the total mass of the raw material for preparing the asymmetric organic carbonate; The carbon-supported metal zinc catalyst is prepared by the following steps: Step 1) Weigh the precursor deep eutectic solvent and zinc acetate according to the mass ratio (5-10):1; Step 2) adding the precursor low eutectic solvent into a container and stirring to preheat, then adding zinc acetate and the precursor low eutectic solvent and stirring to mix, then adding ethylene glycol and continuing to stir until the zinc acetate solid is completely dissolved to obtain a mixed solution; Step 3) placing the mixed solution prepared in step 2) into a tubular furnace, introducing protective gas, heating to 500-800° C. and maintaining the temperature for 1.5-2.5 hours to obtain a crude catalyst; Step 4) grinding the crude catalyst obtained in step 3) to obtain a carbon-supported metal zinc catalyst; The precursor low eutectic solvent is prepared by mixing polyethylene glycol and 2-methylimidazole in a mass ratio of 3: (1.8-2.2).
2. The method for synthesizing asymmetric organic carbonates from biomass-based alcohols according to claim 1, characterized in that: The zinc loading amount in the carbon-supported metal zinc catalyst is 5wt%~30wt%.
3. The method for synthesizing asymmetric organic carbonates from biomass-based alcohols according to claim 1, characterized in that: The specific surface area of the carbon-supported metal zinc catalyst is 238~797m 2 / g; pore diameter 1.7032~3.0968nm, pore volume 0.0272~0.1334cm 3 / g.
4. The method for synthesizing asymmetric organic carbonates from biomass-based alcohols according to claim 1, characterized in that: The heating rate during heating is 5°C / min.
5. The method for synthesizing asymmetric organic carbonates from biomass-based alcohols according to claim 1, characterized in that: The biomass-based alcohol is one of n-hexanol, benzyl alcohol, tetrahydrofurfuryl alcohol, 2-ethylhexanol, 2-ethyl-1-butanol, cyclohexanol and menthol.
Citation Information
Patent Citations
ZIF-8 material-based hydrogenation catalyst and synthetic method thereof
CN104772165A